Occupational risks for renal cancer in Sweden. Issue 2 (February 1987) - McLaughlin, J K; Malker, H S; Stone, B J; Weiner, J A; Malker, B K; Ericsson, J L; Blot, W J; Fraumeni, J F
Abstract : A systematic assessment was made of the occurrence of renal cancer among men by industrial and occupational classification using the Cancer-Environment Registry, which links cancer incidence (1961-79) and census data (1960) with industry and occupation for all employed individuals in Sweden. Data were analysed separately for cancers of the renal parenchyma and pelvis. Significantly increased risks for renal cell cancer were observed for several professional and white collar occupations, including physicians and others in the health care industry. By contrast, the risks for renal pelvis cancer tended to be higher among blue collar workers, especially in the machine industry. Deficits of both cancers occurred among farmers. The findings of the survey are considered as aetiological clues that may deserve further study, although some associations support observations in other countries.